Wood Biomass from the Model Wastewater and Its Fractionation (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The production of veneer in Latvia and many countries of East Europe is accomplished by the hydrothermal treatment of hardwood in special water basins. As a result, formed effluents contain wood-originated pollutants, which are responsible for the enhanced chemical oxygen demand and the intensive colour of the wastewater. Keeping in mind the volume of the polluted effluents formed annually at the Latvian plywood plants, it is very important to extract qualitatively and quantitatively the formed biomass from the effluent. The choose of an effective method of the waste biomass extraction depends on chemical characterisation of the effluent. In this work, for imitating woodworking wastewater, birch sawdust was hydrothermally treated in mild alkaline conditions at 90°C. The yield of the solid biomass did not exceed 7% and contained, mainly, hemicelluloses in the polysaccharide form and lignin. The applied instrumental analysis (FTIR-, UV-, Raman spectroscopy) testify the dominant content of hemicelluloses in the obtained biomass. The fractionation of the biomass was performed using concentrated sulphuric acid and ethanol. As the obtained results have shown, the content of lignin, hemicelluloses and water-soluble degraded wood products in the solid biomass corresponded to the following mass ratio: 1.2 /6.7 /1.0, respectively.